Drastic Ce3+ Insertion Enhancement in YAG Garnet Nanocrystals Through a Solvothermal Route - Cantarano, Alexandra; Testemale, Denis; Homeyer, Estelle; Okuno, Hanako; Potdevin, Audrey; Dujardin, Christophe; Ibanez, Alain; Dantelle, Geraldine (Frontiers in Materials, 2021)
Y3Al5O12 (YAG) nanocrystals have been synthesized by a modified solvothermal method (300°C) allowing the incorporation of cerium ions in much larger proportion (up to 30 mol.% with respect to yttrium ions) than ever published. The reasons are the nanometric size of the produced nanocrystals, allowing to accommodate Ce3+ ions in the rigid YAG structure thanks to the presence of local distortions, and also the soft synthesis route, at low temperatures and far from the thermodynamic equilibrium, which favors the cerium insertion. As a consequence, Ce3+ photoluminescence spectrum can be tuned with the doping concentration, from 541 nm for low Ce3+ concentration to 580 nm for a cerium concentration of 30 mol.%. The internal quantum yield reaches 40 ± 5% before decreasing due to concentration quenching. The nanocrystal brightness, which combines the internal quantum yield and the cerium concentration, has been found optimal for a doping of 2 mol.% Ce3+.